Introduction to the Concept of Sharia Economic Transactions through Children's Financial Literacy Education - Heriyanto, Imron; Hermansyah, Yus; Nurishlah, Laesti; Yudiyanto, Mohamad; Cahyani, Wanda Siti (DPPM Universitas Pelita Bangsa, 2023)
With the significant growth of the Muslim population in various countries, there is a need to increase awareness and understanding of Islamic financial principles, such as the prohibition of usury and the principle of profit sharing. This study aims to analyze how to introduce the concept of sharia economic transactions through children's financial literacy education. The research method used is library research with a qualitative approach. The results of the study show that the implications of sharia economic transactions for society are very broad and positive. By emphasizing justice, transparency, and social responsibility, sharia economic transactions help create a fairer and more prosperous society. Programs such as zakat distribution, microfinancing, and investment in social infrastructure and education contribute to poverty alleviation, economic empowerment, and improving people's quality of life. Financial literacy education for children and adolescents is not only important for their current personal lives, but also for the preparation of a more stable and financially successful future. Continuous training and education on financial literacy integrated with sharia economic values and principles helps strengthen individuals' understanding and practice in adhering to these principles throughout their lives. By using financial literacy as a way to introduce sharia economic transactions, individuals can build a deep understanding of how they can manage their finances in a way that is in accordance with Islamic moral and ethical principles.